Life Cycle Assessment of Construction Components of Schools in Southern Brazil - Rataichesck Fiates, Julia; Ghisi, Enedir (European Journal of Sustainable Development, 2024)
Introducing energy efficiency techniques in schools can significantly reduce energy consumption, as Brazil has a large public education system. The main objective of this work was to select the set of construction components with the lowest environmental impact for use in schools in Florian